Do Lenders Value Corporate Social Responsibility? Evidence from China - Ye, Kangtao; Zhang, Ran (2011)
Drawing on risk mitigation theory, this article examines whether the improvement of firms’ social performance reduces debt financing costs (CDFs) in China, the world’s largest emerging market. Employing both the ordinary least square (OLS) and the two-stage instrumental variable regression methods, we find that improved corporate social responsibility (CSR) reduces the CDF when firms’ CSR investment is lower than an optimal level; however, this relationship is reversed after the CSR investment exceeds the optimal level. Firms with extremely low or extremely high CSR are subject to a higher CDF. The results also suggest that the optimal CSR level for small firms is higher than that for large firms. This study is the first to document a U-shaped relationship between CSR and CDF and also the first to investigate this relationship within an emerging market context.
Keywords: Size; Risk Management; Debt financing cost; Corporate Philanthropy; Corporate Social Responsibility; China